Economic liberalisation in India - Chatterjee, Biswajit (Ed.) (Ahmedabad Allied, 1998)
The present volumes contain sixteen essays on the liberalisation experiments in the Indian economy. The book covers issues on perspective of liberalisation, political economy, taxation and public sector reforms, infrastructure, food security and social ac
Keywords: Economic development-India; India-Economic policy; CompetitionInternational